4K-supporting ARINC818 video transporting and verifying system - Gao Weilin; Yang Bingwei; Xin Chunming (Dianzi Jishu Yingyong)
In demand of 4K or higher resolution video transporting in cockpit in the future, a common system related to ARINC818 video codec is referred and verified through DP video port in this article. The system receives DP video from the computer source,decoded in FPGA, and then packaged the video data according to ARINC818 protocol. The produced ARINC818 video is sent back to the system, decoded in FPGA, and transferred to DP video to display. 10 Gb/s data rate in ARINC818-3 standard is applied in this system, single lane 4K@30 Hz ARINC818 video receiving and dispatching is implemented ,as well as dual lane 4K@60 Hz, characterized with easy to use, feature-rich and flexible configuration.